The Analysis Impact of Bad News and Good News to Stock Return of State-Owned Banks Sebsector in Indonesia Period 2018 - Josephine Surya; Isni Andriana; Rasyid HS Umrie (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2020)
This study aims to determine and analyze the impact of bad news and good news on changes in stock returns of the four state-owned banks of Indonesia, period 2018. The population of this study is consists of four state-owned banks in Indonesia. Using a saturated sampling technique obtained four sample companies. Event study used to examine abnormal return around good news and bad news press release (announcement) date. The analysis technique used is Statistics Descriptive, One Sample Kolmogorov-Smirnov, Paired Sample T-Test, and Wilcoxon Sign Rank Test. There is no significant difference between before and after the press release of bad news. From ninety-six press releases of good news, five press releases showed there is a significant differences between before and after the press release of good news.